PENGARUH EFIKASI DIRI, MOTIVASI KERJA DENGAN DIMEDIASI KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT. BANK BNI SYARIAH KANTOR CABANG PEKALONGAN - Joko Wibowo; Taofik Hidajat (Magister Manajemen STIE Bank BPD Jateng, 2020)
The purpose of this study is to determine and analyze the Effect of Self-Efficacy, Work Motivation, and Mediated by Job Satisfaction on Employee Performance at PT. Bank BNI Syariah Pekalongan Branch Office. The method of this research uses quantitative research with SMART PLS analysis tools. In this study the entire population is also sample because the population are 57 employees, consisting of 34 male and 23 female employees. The results of this study indicate that:There is a positive and significant direct effect of self-efficacy on employee job satisfaction at PT. Bank BNI Syariah Pekalongan Branch Office.There is a positive and significant direct effect of work motivation on employee Job Satisfaction at PT Bank BNI Syariah Pekalongan Branch Office.There is a positive and significant direct effect of self-efficacy on employee performance at PT. Bank BNI Syariah Pekalongan Branch Office.There is a positive and significant direct effect of work motivation on employee performance at PT. Bank BNI Syariah Bank Pekalongan Branch Office.There is a positive and significant direct effect of employee job satisfaction on employee performance at PT. Bank BNI Syariah Pekalongan Branch Office.There is a positive and significant direct effect of job satisfaction is able to mediate self-efficacy on employee performance at PT. Bank BNI Syariah Pekalongan Branch Office.There is a positive and significant direct effect of job satisfaction is able to mediate work motivation on employee performance at PT. Bank BNI Syariah Pekalongan Branch Office